2011
DOI: 10.1177/0486613411418049
|View full text |Cite
|
Sign up to set email alerts
|

“Gender Trouble”

Abstract: This paper explores the relationship between gender equality and economic democracy in worker cooperatives in the United States. A specific method for analyzing women's status in worker cooperatives is proposed. Preliminary findings from a small-scale survey of U.S. worker cooperatives in 2001 are presented, showing that despite the egalitarian nature of cooperatives several gender inequalities persist. JEL classification: J54, B54, P13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Evidence from this study confirms that the so-called dyad gender composition of both managers and employees has an effect on participation (Ayman et al, 2009). This study reinforces the results of previous findings: men and women have significantly different orientations leading to gender differences in the effects of participation initiatives (Olorunsola and Olayemi, 2011; Miller, 2012; Gallie, 2013; Sarafidou and Chatziioannidis, 2013). In this respect, male supervisor support has a positive and high influence when dealing with female employees.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Evidence from this study confirms that the so-called dyad gender composition of both managers and employees has an effect on participation (Ayman et al, 2009). This study reinforces the results of previous findings: men and women have significantly different orientations leading to gender differences in the effects of participation initiatives (Olorunsola and Olayemi, 2011; Miller, 2012; Gallie, 2013; Sarafidou and Chatziioannidis, 2013). In this respect, male supervisor support has a positive and high influence when dealing with female employees.…”
Section: Discussionsupporting
confidence: 91%
“…Beyond managerial stereotypes, some studies have analyzed gender from employee perspectives. Some of them confirm significant differences between men and women in participation (Olorunsola and Olayemi, 2011; Miller, 2012; Sarafidou and Chatziioannidis, 2013). Most of these studies find that women participate less in decision making than men (Markey et al, 2002; De Acedo Lizárraga et al, 2007; Chalchissa and Emnet, 2013).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…From the human resources perspective, the current paper focuses on PDM as direct employee participation, which is referred to as an employer-leading tool that allows employees to take part in decision-related operational and organizational matters. This definition is supported by [14,15], who indicate that employee participation refers to the extent to which employees are allowed or encouraged to share their views and ideas about organizational activities or provide their input in organizational decision making. The present study intends to explore whether there are noticeable differences among all the determinant variables and the scope of the decision.…”
Section: Participative Decision Making (Pdm)mentioning
confidence: 99%
“…Different benefits are attributed to employee participation. Miller [14] states that the most widely studied attitudinal outcome of employee participation is job satisfaction. Additionally, other outcomes that previous studies have found to be associated with employee participation are job performance, organizational commitment, job involvement, and productivity [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%